TAX AVOIDANCE: STUDI EMPIRIS PADA PERUSAHAANMANUFAKTUR SEKTOR BARANG KONSUMSI DI INDONESIA - Giawan Nur Fitria; Riaty Handayani (Monex: Journal of Accounting Research, 2019)
This purpose of this study is to examine the effect of Return On Asset (ROA), Company’s Size, Audit Commitee and Proportion of Independent Directors to Tax Avoidance. Tax Avoidance is measured using the cash effective tax rate (CETR). This study is an empirical research with the purposive of sampling techniques in data collection. Secondary data obtained from financial statement and annual report listing on the Indonesia Stock Exchange period 2013-2017. The sample was 21 manufacture companies on consumption sector listed in Indonesia Stock Exchange period 2013-2017. Multiple regression analysis was conducted using SPSS version 23.00 for windows. The test results showed of four hypotheses proposed hypothesis two accepted hypothesis. And the amount of determination of the case (adjusted R2) of 12,5%. Key words: Return On Asset, Company’s Size, Audit Commitee, Proportion of Independent Directors and Tax Avoidance.